Dairy development for the resource poor. Part 2: Kenya and Ethiopia. Dairy development case studies - Staal, Steven J.; Nin-Pratt, Alejandro; Jabbar, M.A. (Food and Agriculture Organization of the United Nations, 2008)
The process of dairy development that this study addresses is driven by underlying fundamental changes in economic growth, the value of resources and consumer demand. However, it is also shaped by public policies, interventions and investment decisions and will be accompanied by changes in impact on incomes, opportunities and livelihoods of producers and changes in opportunities and returns for market agents and investors. This study examines dairy development in two key dairy producing regions in the developing world: East Africa and South Asia. The aim of the study is to analyse the trends in dairy development in these two regions and identify their key determinants, to analyse the impact of policy interventions on those trends and to identify impacts of dairy development, particularly on the poor. The study is reported in three parts: Part 1 presents a conceptual framework for dairy development, followed by a section presenting a regional analysis of dairy development trends across all the countries in the two regions and a synthesis of the outcomes of the case study analyses (see below), highlighting implications for policy interventions and investment, including proposing a model for pro-poor dairy development. Parts 2 and 3 consist of in-depth case studies and analyses of dairy development trends, determinants and outcomes in Kenya and Ethiopia (Part 2 – this report) and India and Pakistan (Part 3).